(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
Today, along with all spheres of public life, attention is paid to the development of the educational system at the level of Public Policy.The issue of technologizing the improvement of the higher education system with educational processes that are clearly, scientifically based, compiled from separate technological projects, algorithmic, guaranteeing a certain result, diagnostic orientation to the goals set is of urgent importance.